MR imaging features and contrast enhancement characteristics in benign and malignant breast lesions - Hoon, TS; Ansari, MA; Shuaib, IL; Ariff, AR Mohd; Khalid, I; Basheer, MB L Mohd; Tun, M; Aziz, Mohd E (Journal of Institute of Medicine Nepal, 2013)
Introduction: Breast cancer is the commonest female malignancy in Malaysia and other countries the world. All races are affected in Malaysia and breast cancer comprised 30.4% of all newly diagnosed cancer cases. A women in Malaysia has a 1 in 19 chances of getting breast cancer in her lifetime. The Age Standardized Rate (ASR) of female breast cancer in Malaysia is 52.8 per 100,000 people and is higher than that in Singapore, Hong Kong and Shanghai, but it is lower than that in Australia and the UK. Out of the 4,337 new cases of female breast cancer cases reported to the National Cancer Registry of Malaysia in 2002, 52.3% were for women less than 50 years old. Genetic risk factors have not been studies thoroughly in Malaysia. Methods: We prospectively studied 55 patients with breast lumps in whom MR imaging was performed. The T1- and T2-weighted, axial STIR, fat-suppression contrast enhanced fast spin echo and two dimensional dynamic enhanced fast spoiled gradient-echo images were obtained. The tumour margins and shape, enhancement pattern and time-signal intensity curves were analysed. Results: A total of 37 patients fulfilled the study criteria with the mean age of 43.46 ±11.99 years (age ranged 21-70). There were 23 benign and 14 malignant lesions. The MR imaging criteria suggestive of malignancy were poorly defined and spiculated margins, irregular shape, heterogeneous and rim enhancement as well as type II and III curves. On the other hand, the criteria for a benign breast lesions were well-defined margin, regular and lobulated shape, none or homogeneous enhancement and type I curve. Only the malignant lesions are characterised by skin, retroareolar, nipple and pectoralis muscle involvement. Conclusion: MR imaging is a valuable complementary breast imaging tool to further evaluate equivocal findings on conventional x-ray mammography. A combination of lesion morphology and enhancement characteristics is useful in distinguishing benign from malignant lesions. DOI: http://dx.doi.org/10.3126/joim.v34i2.9052 Journal of Institute of Medicine August, 2012; 34:2 28-34